More Stable, More Generous Banks? The Relationship between Financial Performance and Dividend Policy - Nadya Kamila; Ossi Ferli (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to analyze the effect of leverage aniani4d, profitability, liquidity, profit growth, and firm size on dividend policy in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The analysis method used is multiple linear regression to identify the influence of independent variables on dividend policy. The population in this study consists of all banking companies listed on the IDX, with 12 companies selected as samples using a purposive sampling method. The results show that leverage (DER), profitability (ROA), and firm size (FS) have a positive influence on dividend policy (DPR). Conversely, profit growth (PG) has a negative effect on dividend policy, while liquidity (CR) has no significant effect. Based on these findings, it is recommended that management maintain stable net income to ensure the company’s ability to pay dividends. This can be achieved through income diversification, operational efficiency, and a balanced profit allocation strategy. The novelty of this research lies in the change in the sector analyzed, namely the banking sector, as well as the extension of the analysis period covering five years (2019-2023). In addition, this study replaces the growth variable with Profit Growth to more accurately describe the company's potential to generate sustainable income. The variables analyzed in this study include Debt to Equity Ratio (DER), Return on Asset (ROA), Current Ratio, Profit Growth, and Firm Size.